2022
DOI: 10.1177/15248380221082079
|View full text |Cite
|
Sign up to set email alerts
|

Vicarious Post-traumatic Growth in Professionals Exposed to Traumatogenic Material: A Systematic Literature Review

Abstract: Repeated exposure to traumatogenic material as part of work with traumatised individuals can have detrimental effects on professionals’ well-being. Growing research has explored this phenomenon, known as ‘vicarious traumatisation’. Nevertheless, little research has focused on the positive effects of this work on professionals, namely, ‘vicarious post-traumatic growth’. This literature review aims to identify existing research demonstrating mental health professionals’ experiences of growth, along with environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 61 publications
(149 reference statements)
0
4
0
Order By: Relevance
“…In a recent and comprehensive systematic literature review of post‐traumatic growth studies, findings indicate that adversity is necessary for personal growth. Post‐traumatic growth evolves from rising to the challenge of the adversity and the consequent new and positive or productive meanings that are created based on the practitioner's reflection on the experience (Tsirimokou et al, 2023). However, Tsirimokou et al also note that increased and continuous exposure to trauma is connected to lower levels of growth, suggesting that prolonged and consistent exposure to trauma over the practitioner's career has a diminishing growth effect.…”
Section: Reactive Traumatic Stress: Contributing and Protective Factorsmentioning
confidence: 99%
“…In a recent and comprehensive systematic literature review of post‐traumatic growth studies, findings indicate that adversity is necessary for personal growth. Post‐traumatic growth evolves from rising to the challenge of the adversity and the consequent new and positive or productive meanings that are created based on the practitioner's reflection on the experience (Tsirimokou et al, 2023). However, Tsirimokou et al also note that increased and continuous exposure to trauma is connected to lower levels of growth, suggesting that prolonged and consistent exposure to trauma over the practitioner's career has a diminishing growth effect.…”
Section: Reactive Traumatic Stress: Contributing and Protective Factorsmentioning
confidence: 99%
“…Several studies have reported negative outcomes of the COVID‐19 pandemic for healthcare workers, such as anxiety symptoms, depression, insomnia, high levels of stress and post‐traumatic stress disorder (Batra et al., 2020; Spoorthy et al., 2020). However, besides these negative effects of the COVID‐19 pandemic, several constructive outcomes have been observed, such as post‐traumatic growth (PTG) (Tsirimokou et al., 2022). PTG refers to the positive psychological changes experienced while struggling with traumatic negative life events and situations (Tedeschi et al., 2017).…”
Section: Introdctionmentioning
confidence: 99%
“…Like PTG, SPTG consists of positive changes in psychosocial functioning which relate to self-perception, relationships with others, and philosophy of life [5,6,[16][17][18][19][20]. However, despite their similarities, SPTG and PTG are not identical constructs, and some differences between them can be distinguished in appreciation of their own work and spiritual sphere [17,21]. The SPTG has also been observed as a positive effect of working with victims of traumatic experiences, and this seems to be an important indicator that influences the quality and effectiveness of the work done [22].…”
Section: Introductionmentioning
confidence: 99%